A Review on Medicinal Plants of North Eastern Region with Potential Antifertility Activity - Goswami, Priyanka; Laskar, Moksood Ahmed; Basak, Mrinmoy (Asian Journal of Pharmaceutical Research and Development, 2020)
The increase in population is becoming a comprehensive problem, causing much pressure on economic, social and natural assets. Oral contraceptive agents have improved the rate of infertility but their unusual side effects limit the use. Current antifertility therapy lacks satisfactory success due to this adverse effect; hence, patients are seeking complementary and alternative medicine for anti-fertility action. Ayurveda and other Indian literature mention the use of plants in various human ailments. India has about more than 45000 plant species and among them several thousand are claimed to possess medicinal properties. Researchers conducted in the last few decades on the plants mentioned in ancient literature or used traditionally for anti-fertility action. This review reveals that some plants and their part used having anti-fertility action, which are helpful for researcher to develop new herbal anti-fertility formulations. In the recent years, interest in drugs of plant origin has been progressively increased. The aim of this review is to highlight the work on anti-fertility of plant origin. For women who can’t use modern forms of contraception due to adverse effect or other reasons, therefore herbs can offer alternatives and reducing fertility would be better than other contraceptives. This article may help investigators to identify medicinal plants responsible for anti-fertility activity.